The Middle Eastern Wealth Management Industry: Boon or Bust? - Bryane Michael; Nenad Apostoloski (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The wealth management industry has expanded greatly in the Middle East – following the fortunes of wealth itself. How can wealth managers identify and grow their portfolios in this region? What policies can they push for in order to build wealth management and private banking services? What threats does ordinary retail business pose to the premium model?
Keywords: G21; F23; 330; wealth management; middle east; Private banking; Middle East